Is Policy Well-Targeted to Remedy Financial Strain among Caregivers of Severely Injured U.S. Service Members? - Courtney Harold Van Houtven; Greta Friedemann-Sánchez; Barbara Clothier; Deborah Levison; Brent C. Taylor; Agnes C. Jensen; Sean M. Phelan; Joan M. Griffin (SAGE Publishing, 2012)
U.S. military service members have sustained severe injuries since the start of the wars in Iraq and Afghanistan. This paper aims to determine the factors associated with financial strain of their caregivers and establish whether recent federal legislation targets caregivers experiencing financial strain. In our national survey, 62.3% of caregivers depleted assets and/or accumulated debt, and 41% of working caregivers left the labor force. If a severely injured veteran needed intensive help, the primary caregiver faced odds 4.63 times higher of leaving the labor force, and used $27,576 more in assets and/or accumulated debt compared to caregivers of veterans needing little or no assistance.